Models and a deformations simulation approach using ANSYS CAD for railway wagons weighing system - Denisenko, M.A.; Isaeva, A.S.; Sinyukin, A.S.; Kovalev, A.V. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
Possibility of fast, convenient and precise definition of wagons load mass allows enhancing transport safety and ensures assets accounting in railroad infrastructure. There are known three-dimensional solid models of railway track sector and approaches of simulation the deformation which emerge in rails by mechanical load effect transmitted through wagon wheels. In accordance with these approaches, emerging deformations are recomputed into wagons weight. The rail temperature influences on its mechanical properties and, consequently, on the deformation value. In this work, for the first time, a technique has been proposed that allows one to consider the deformation of the rail under the load influence, taking into account its temperature variance at different boundary conditions. According to the proposed approach, the wagon weight is defined by deformation values which are measured by strain gauges located on the rail web. The developed models include a rail wheel, ties and a rail fragment. The rail fragment corresponding to the railway track sector on which sensors are mounted geometrically replicates an existent rail type R50 and is situated on the ties fixed from bottom side. The wheel model complies with an existent solid-rolled wagon wheel type with tread diameter 920 mm, thereby correct contact patch retains in the model. According to the approach, finite-element mesh is generated on the developed solid models, connections between model fragments are established, and boundary and temperature conditions as well as acting forces are applied. Sequentially finite-element analysis is performed for all possible combination of wheel coordinate, load mass and temperature. For every case, deformation values are registered in four rail nodes corresponding to strain gauges placements. Comparison of finite-element analysis results for two developed solid models is carried out. The models differ by the way of the rail on the ties mounting and boundary condition setting on the end faces of the rail fragment, allowing to consider possibility of temperature stresses relaxation. In the model 1 the rail is connected with ties rigidly, in the model 2 the rail and the ties are connected by a contact allowing the rail motion along the tie with given friction coefficient. Besides that clamp bolts impact is imitated in the model 2. The approach is implemented within multiphysical simulation environment ANSYS for coupled three-dimensional problem using Static Structural and Steady-State Thermal modules. Simulation results showed that the deformation values determined by the temperature influence differ for the proposed models. Vertical deformations range of the rail fragment on which the strain gauges are fastened, at the mass 12,500 kg loaded on the wheel, is from –245 μm (bend down) to 15 μm (bend up) for the model 1 depending on the rail temperature (in the range from –20 °C to +50 °C) and from –225 μm to –100 μm for the model 2. This allows concluding that the model 2 reflects deformation process more correctly, and the temperature influence on the deformation is less relevant compared to mechanical load value. The proposed model in contrast to the known ones implies static weighing characterized by more accuracy, reliability and simplicity of use. In the future it is planned the executing of the more detail research of a model with two wheels and an axle for determining optimal simulation time and obtained results accuracy.